The Effect of Current, Cr2O3 and MnO2 Active Flux to The Depth of Penetration and Microstructure of A-TIG 5083 Aluminium Welding - Eriek Widodo; Moch. Karim Al Amin; Dika Anggara; Imah Kusminah; Alvalo Wibowo; Ridhwan Haliq; Muhammad Nashruddin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Materials with a thickness exceeding 5 mm require at least two layers of TIG welding; however, this challenge can be addressed through A-TIG welding. A-TIG welding utilizes an active flux to increase penetration without requiring changes to welding parameters. This research investigated the effects of current intensity and the use of Cr2O3 and MnO2 active fluxes on depth of penetration, microstructure, and hardness. The study employed A-TIG welding on 5083 aluminum with current variations of 100 A, 130 A, and 160 A. Results indicated that Cr2O3 active flux at a current of 160 A achieved the deepest penetration of 5.7 mm, while MnO2 at 100 A yielded the highest average hardness of 77.96 kgf/mm2. Regarding microstructure, no significant changes were observed in the base metal across both fluxes; however, grain growth in the weld metal was more pronounced than in the Heat Affected Zone (HAZ) and base metal. Ultimately, Cr2O3 provided greater depth of penetration and a more dispersed distribution of Mg2Si precipitates, whereas MnO2 demonstrated a superior effect on hardness compared to Cr2O3.